Distinctive dust weather intensities in North China resulted from two types of atmospheric circulation anomalies - Q. Huo; Q. Huo; Z. Yin; Z. Yin; Z. Yin; X. Ma; X. Ma; H. Wang; H. Wang; H. Wang (Atmospheric Chemistry and Physics)
Dust weather in North China (NC; 34–42° N, 105–120° E) has worsened in recent years, posing adverse impacts on the environment, human health, and the economy. A super dust storm that occurred on 15 March 2021 raised Beijing's PM10 (particulate matter with a diameter less than 10 µm) concentrations above 7000 µg m−3, while 2023 witnessed the highest spring dust weather frequency in nearly a decade. Previous research has primarily focused on the role of the Mongolian cyclone in influencing dust weather in NC, with less attention given to other synoptic systems. Additionally, the differences in PM10 concentrations in NC caused by different synoptic systems have not yet been quantified. This study demonstrates that the Mongolian cyclone was responsible for 61.7 % of the dust weather in NC, while the remaining 38.3 % was primarily caused by the cold high. The dust intensity induced by the Mongolian cyclone was stronger than that of the cold high, with average maximum PM10 concentrations of 3076 and 2391 µg m−3, respectively. The three-dimensional structure of atmospheric circulation anomalies and related dynamic mechanisms of the two types were concluded. To comprehensively forecast the two types of dust weather, a common predictor was constructed based on the 500 hPa cyclonic anomaly and anticyclonic anomaly circulation systems. These findings contribute to enhancing the comprehension of dust weather in NC and offer insights for both dust weather forecasting and climate prediction.